Double-voicing at Work - Baxter, J. author. aut Link
VIII, 120 p.
Keywords: This book reveals how 'double-voicing' is an inherent and routine part of spoken interactions within institutional contexts. Baxter's research shows that women use double-voicing more than men as a means of gaining acceptance and approval in the workplace. Double-voicing thus involves an interplay between power, gender and linguistic expertise.